Optimizing images - Hogan, Lara Callender (O'Reilly, 2017)
Uncover the best practices for use and optimization for each file type. Included in this excerpt are techniques to optimize the way images are loaded into web pages, such as spriting or replacing them with CSS or SVG. Lastly, we'll cover what you can do to increase the longevity of your optimized image solutions, including implementing style guides or automated workflows for image compression.